2002
DOI: 10.1016/s0736-0266(01)00179-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of adsorbed endotoxin in particle‐induced stimulation of cytokine release

Abstract: Numerous in vitro models have demonstraed the capacity of wear particles to stimulate the release of soluble pro‐inflammatory products with the ability to induce local bone resorption. Recent observations have demonstrated that binding of lipopolysaccharide (LPS) to particulate wear deris can significantly modulate the pattern of cell response in the in vitro models. These findings raise concerns over the possible role of LPS in the athogenesis of aseptic looseing after total joint replacements, and also indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 56 publications
3
92
0
4
Order By: Relevance
“…The polyethylene wear rate was greater in osteolysis-susceptible subjects then in the controls, and the severity of pelvic osteolytic defects by AAOS grade was strongly correlated with polyethylene wear rate. The above findings are consistent with other investigators who have shown that the biological activity of particulate wear debris is strongly dependent on adherent endotoxin, 18 that ex vivo responses of human PBMCs to particulate stimuli can be affected by the presence of indwelling metallic prostheses, 19 and that polyethylene wear rate modulates both the risk of osteolysis, and the severity of osteolytic lesions. 6 For these reasons polyethylene wear rate and clinical titanium exposure were included as covariates in our multivariate analysis model.…”
Section: Immune Response In Osteolysis-susceptible Patientssupporting
confidence: 92%
“…The polyethylene wear rate was greater in osteolysis-susceptible subjects then in the controls, and the severity of pelvic osteolytic defects by AAOS grade was strongly correlated with polyethylene wear rate. The above findings are consistent with other investigators who have shown that the biological activity of particulate wear debris is strongly dependent on adherent endotoxin, 18 that ex vivo responses of human PBMCs to particulate stimuli can be affected by the presence of indwelling metallic prostheses, 19 and that polyethylene wear rate modulates both the risk of osteolysis, and the severity of osteolytic lesions. 6 For these reasons polyethylene wear rate and clinical titanium exposure were included as covariates in our multivariate analysis model.…”
Section: Immune Response In Osteolysis-susceptible Patientssupporting
confidence: 92%
“…These findings are supported by another study (Chiang et al 1999) showing that LPSinduced bone resorption is substantially mediated by TNFα and IL-1 receptor signaling. Moreover, the different time courses of expression of mRNA for OPG and RANK between groups indicate that the particle effects demonstrated are not due to LPS-contaminated particles or particle-associated endotoxin, as has been postulated by other authors (Bi et al 2001, Brooks et al 2002, Cho et al 2002.…”
Section: Discussionsupporting
confidence: 66%
“…The protocols we followed for sterilization and endotoxin removal for both titanium and polyethylene particles were different than in studies published by other investigators [5,8,13,15,18,20]. We used loo'%, ethanol for 48 h for sterilization and significant reduction of endotoxin.…”
Section: Discussionmentioning
confidence: 99%